Jeremiah Evarts collection - Evarts, Jeremiah, 1781-1831.
Principally correspondence between Evarts and such individuals as Rufus Anderson, Timothy Dwight, Theodore Frelinghuysen, John Jay, and Daniel Webster relating to foreign missions and opposition to Andrew Jackson's Indian policy. Also includes some financial items.
Chiefly photocopies.
Lawyer, editor, and philanthropist.
Collection material in English.
Keywords: Anderson, Rufus, -- 1796-1880 -- Correspondence; Dwight, Timothy, -- 1752-1817 -- Correspondence; Frelinghuysen, Theodore, -- 1787-1862 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Jay, John, -- 1745-1829 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Indians of North America -- Government relations; Missions; Editors; Lawyers; Philanthropists